Multiple processes drive genetic structure of humpback whale ( Megaptera novaeangliae ) populations across spatial scales - Francine Kershaw; Inês Carvalho; Jacqueline Loo; Cristina Pomilla; Peter B. Best; Ken P. Findlay; Salvatore Cerchio; Tim Collins; Marcia H. Engel; Gianna Minton; Peter Ersts; Jaco Barendse; et al. (Molecular Ecology, 2017)
Elucidating patterns of population structure for species with complex life histories, and disentangling the processes driving such patterns, remains a significant analytical challenge. Humpback whale ( Megaptera novaeangliae ) populations display complex genetic structures that have not been fully resolved at all spatial scales. We generated a data set of nuclear markers for 3575 samples spanning the seven breeding stocks and substocks found in the South Atlantic and western and northern Indian Oceans. For the total sample, and males and females separately, we assessed genetic diversity, tested for genetic differentiation between putative populations and isolation by distance, estimated the number of genetic clusters without a priori population information and estimated rates of gene flow using maximum‐likelihood and Bayesian approaches. At the ocean basin scale, structure is governed by geographical distance ( IBD P F ST 0.034–0.161; P